Relações e interações raciais entre universitários negros e brancos no curso de Pedagogia e Direito da UFMT : (re) construção de identidades na contemporaneidade - Batista, Michelangelo Henrique (2019)
The research carried out, which resulted in the present doctoral thesis, is linked to the line of research Social Movements, Politics and Popular Education, and to the Quilombola Education Study and Research Group - PPGE / UFMT. The thesis was prepared to answer the following problem: How did the identity reconfiguration process take place in the context of the academic community as a quota student? An answer to this question was sought in the social and racial relations and interactions of black and white university students, from the Pedagogy and Law Courses at the Federal University of the State of Mato Grosso - UFMT. The objective was to understand the construction and reconstruction of identities of black university students in the context of relationships and interactions with white university students in the Pedagogy and Law Courses at UFMT. The case study method was used, with a qualitative approach, applying two research techniques for data collection, dividing the empirical research into two stages. In the first stage, a questionnaire was used for all university students in the Pedagogy and Law courses. In the second stage, a semi-structured interview was applied to five university students from the Pedagogy Course and five from the Law Course, all of whom were racial quota students, social quota students and non-quota students. Still in a methodological perspective, the concepts of field, habitus and social structure were used from Bourdieu (1989). Almeida (2018), the racial habitus conception in Miranda (2017) and Monsma (2013) were used as central theoretical foundations and, regarding the context of affirmative actions, we opted for the concept of oxygenation of Santos (2016). The research showed that racial identities are built in social and racial relationships and interactions, submerged in power relations, relationships that are not limited to an explicit hierarchical constitution, in which there is the action of a single force, the dominant one, but, rather, , the action also of a counter-hegemonic force, a force founded on affirmative ideological political logic, the product of the struggles and conquests of black movements, intellectuals, groups and research centers that promote an anti-racist struggle. This counter-hegemonic force is in the ascendant and opposes the ideological political logic of money laundering, which is shaped by the mythical racial democracy that unfolds in a dominant racial habitus built since the genesis of the constitution of the Brazilian State. Thus, the results corroborated for a credible thesis of identity construction based on multiple identity notions, showing in which power relations they are submerged and how the subjects move from one notion of identity to another, dynamizing themselves identitatively in the social and racial context.